Redescription and variation of Micrurus paraensis Cunha & Nascimento 1973 (Serpentes: Elapidae) - Feitosa, Darlan Tavares; Da Costa Prudente, Ana Lúcia; de Lima, Ana Caroline (Zootaxa, 2007)
A Neotropical snake, Micrurus paraensis Cunha & Nascimento 1973 from east of Pará state, Brazil is described. This snake is found in secondary forest vegetation and remnants of tropical rainforest in Suriname, and Brazil from Pará, Maranhão, Mato Grosso and Rondônia states. Some authors disagree about the validity of the specific status and they prefer to maintain the subspecific status. The objective of this paper is to enlarge the knowledge about M. paraensis morphology with a description of new systematic characters. External morphology of 64 specimens were analyzed. The species is characterized by the number of black bands on body (12 to 21) and by having a black cap beginning on rostral. The hemipenis is long and bifurcated.